Refleksi Filosofi Keilmuan atas Sistem Pengelolaan Data Karyawan - Winata, Andreas (Indonesian Character Journal, 2025)
Employee data management system or often known as Human Resources Information System (HRIS), is a system to manage employee data. This study discusses the evolution of HRIS through the Thomas Kuhn’s paradigm theory, which suggest that scientific progress is not linear but evolve through phases of normal science and paradigm shifts. The initial paradigm of HRIS involved a simple and manual spreadsheet system, which then shifted to an integrated HRIS platform due to anomalies and crisis. The method used in this study is philosophical, especially phenomenology, to explore the characteristic, anomaly and paradigm shifts in HRIS development. The implementation of the new technologies such as AI and Edge Computing is proposed to address new anomalies, driving further innovation. This study concludes that changes in HRIS are part of dynamics of the development of science and technology that continues to grow.